[PP.12.02] COMPARISON OF PERINDOPRIL/AMLODIPIN FIXED DOSE COMBINATION INFLUENCE ON TARGET ORGAN DAMAGE IN HYPERTENSIVE PATIENTS WITH AND WITHOUT ISCHEMIC HEART DISEASE: (EPHES TRAIL). (September 2017) - Radchenko, G.; Mushtenko, L.; Torbas, O.; Kushnir, S.; Yarinkina, O.; Potashev, S.; Sirenko, Yu.
Abstract : Objective: The aim of study was to compare the efficacy of fixed-dose combination (FDC) perindopril + amlodipine in blood pressure (BP) decreasing and target organ damage in patients with arterial hypertension (AH) with and without IHD. Design and method: There were included 60 patients (aged > 30 years) with AH: 1st group included 30 patients without IHD, 2nd group – 30 patients with IHD. All patients were administered perindopril/amlodipine in daily baseline dose 5/5 mg with up-titration to 10/10 mg. If target BP was not achieved (>140/90 mmHg) after 6 weeks the indapamide 1.5 mg was added. Statins, beta-blockers and acetylsalicilic acid were allowed. All patients were done: office and ambulatory BP measurements, pulse wave velocity (PWV) and central SBP, augmentation index adjusted to heart rate 75 (Aix75), ECG, Doppler-EchoCG, ankle-brachial index, intima-media thickness (IMT). The follow-up period was 12 months. Results: Therapy based on FDC was effective in BP lowering (office, ambulatory, aorta) in both groups. Baseline increased day- and night-time BP variability, morning surge of SBP and 'non-dipper' rate decreased in both groups, but in IHD patients these patterns were significant higher. On therapy Aix75 decreased significantly in both groups, but in 2nd group it was less in comparison with 1st group. FDC provided improving of PWVe and diastolic left ventricular function, decreasing of albuminuria, left ventricular hypertrophy and left atrium size. Lowering of PWVe was significant (p < 0.005) less in patients without IHD, than with IHD –2.5 ± 0.2vs4.4 ± 0.5 m/s. The positive dynamic of deltaE/A and deltaE/E' was more in patients with IHD than in without IHD-64.4 and 54.1% vs 39.8 and 23.2% (p < 0.05 for both comparisons). IMTmax decreased significantly only in patients with IHD. In group of IHD we noted significant decreasing of angina episode rate-from 2.5 ± 0.4 till 1.2 ± 0.2 (p < 0.01) per week. Conclusions: Thus FDC perindopril/amlodipin was effective in BP decreasing and in target organ damage regression in groups with and without IHD signs. But dynamic of target organ damage changes was some different in groups.